An investigation of micro aerial vehicles (µAV) - Swetha, S; Anandan, R; Kalaivani, K (International Journal of Engineering and Technology, 2018)
Quadcopter UAV also known as quadrotor  is the  another form of helicopters having more spirited firmness than helicopters. They play a paramount role in divergent areas like military operations, surveillance, fire sensing and some important areas having many complications. Quadcopters are UAV's with capability of perpendicular takeoffs, arrivals and drift at a crave location. This survey paper addresses the delineation and evolution of a proclivity arm quadcopter for mini payload and longtime endurance.